1986
DOI: 10.1007/bf02348111
|View full text |Cite
|
Sign up to set email alerts
|

Soldiers of a European gall aphid,Pemphigus spyrotecae (Homoptera: Aphidoidea): Why do they molt?

Abstract: Abstract-A non-migratory aphid, Pemphigus spyrothecae, produces l st-instar larvae of 2 types in the gall: thick-legged ones and normal-legged ones. It was found that the thick-legged larvae play a defensive role, hence they may be called soldiers. Unlike the soldiers of other species hitherto reported, at least some soldiers of this species molt and become adults. Their incomplete sterility is explained historically:1) The migratory ancestor of P. spyrothecae once produced monomorphic l st-instar larvae attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
2
30
0
3
Order By: Relevance
“…We proposed that the non-migratory life cycles of these Pemphigus species have evolved through generation packing (GP): in the migratory ancestor of a non-migratory Pemphigus species a mutation that caused alate .emigrants to Iarviposit in the gall (instead of on the secondary host) occurred and was fixed, and the "emigrants" were later transformed into apterae. Morphological data for P. spyrothecae (Aoki & Kurosu 1986) and P. monophagus (Aoki & Kurosu 1988a) accord well with what the GP hypothesis predicts.As a result of GP, 2 types of (lst-instar) larvae coexist in the gall of a non-migratory species. Larvae of one type are original gall inhabitants, and those of the other type had once lived on the secondary host, and were packed into the gall.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…We proposed that the non-migratory life cycles of these Pemphigus species have evolved through generation packing (GP): in the migratory ancestor of a non-migratory Pemphigus species a mutation that caused alate .emigrants to Iarviposit in the gall (instead of on the secondary host) occurred and was fixed, and the "emigrants" were later transformed into apterae. Morphological data for P. spyrothecae (Aoki & Kurosu 1986) and P. monophagus (Aoki & Kurosu 1988a) accord well with what the GP hypothesis predicts.As a result of GP, 2 types of (lst-instar) larvae coexist in the gall of a non-migratory species. Larvae of one type are original gall inhabitants, and those of the other type had once lived on the secondary host, and were packed into the gall.…”
supporting
confidence: 76%
“…However, neither P. spyrothecae nor P. monophagus has such intermediate-like lst-instar larvae (Aoki & Kurosu 1986, 1988a.…”
mentioning
confidence: 99%
“…Aoki (1978) and Aoki and Kurosu (1986) found that fertile defensive larvae appear in the galls of Pemphigus dorocola and P. spyrothecae. Heie (1980) and Aoki and Kurosu (1988b) reported that the colonies of both species last much longer than those of other Pernphigus species without defenders (for P. dorocola, from early July to November; for P. spyrothecae, as late as November).…”
Section: Evidencementioning
confidence: 98%
“…The species is monoecious holocyclic and winged sexuparae emerge in AugustNovember to produce sexuals on the bark of the trees (Lampel 1960). First instar nymphs with thick forelegs function as soldiers and defend the gall against predators (Aoki andKurosu 1986, Foster 1990), repair the gall (Pike and Foster 2004) and remove waxcoated droplets of honeydew (Pike et al 2002). The species is widely distributed in Europe, in North Africa (Tunisia), Western Siberia, Pakistan and introduced into Canada [Blackman and Eastop (1994) It is a holocyclic, heteroecious species and the fundatrix makes galls on leaves of P. nigra which originate from the mid-rib at the base of the upper side of the leaf.…”
Section: Pemphigus (Pemphigus) Bursarius (Linnaeus 1758) (Eriosomatimentioning
confidence: 99%